Seroprevalence of neutralizing antibodies against adenovirus types C5, D26 and B35 in Burkina Faso and Chad : Impacts on the use of adenovirus-derived vectors in a vaccination context - (:unkn) unknown (My University, 2021)
Adenoviruses (HAdV) are generally responsible for mild infections in immunocompetent individuals, but they are also powerful therapeutic tools for gene transfer, principally in the context of vaccination. With the COVID-19 pandemic, Adenovirus-derived vectors (HAdve) are now an integral part of the vaccine landscape; however, their development and use were not without obstacles and risks. Generally, the immunogenicity of virus-derived vectors is an obstacle for gene transfer, as it reduces the intensity and time of transgene expression. Another major obstacle is pre-existing host immunity, in particular the humoral component with the presence of neutralizing antibodies (NAb), as illustrated by the failure of Merck's HTNC502 HIV vaccine trial. Not only the vaccine HAdV-C5-derived failed to protect again HIV, but it also led to an increased susceptibility to HIV infection in patients with a high humoral preexisting immunity to HAdV-C5. Strategies to circumvent these obstacles include the use of adenoviral vectors of animal origin or human "alternative" vectors with low seroprevalence. Objectives of my thesis were to determine the seroprevalence of NAb directed to "alternative" HAdV (HAdV-D26 and B35) compared to HAdV-C5, in sub-Saharan African populations. We also evaluated the impact of NAb on the on the host immune response using an experimental in vivo model of dendritic cell (DC) activation. Our results show a high seroprevalence for HAdV-C5 in France and sub-Saharan Africa, while we found high Nabs titers for HAdV-D26 only in African samples. The seroprevalence of HAdV-B35 was low for all populations tested. Our model of DC activation suggests that the use of HAdV-D26-derived vaccines in sub-Saharan African populations leads to a strong activation of the host immune response, particularly for populations living with HIV. My thesis work highlights our weaknesses concerning global HAdV seroprevalence, in particular for vulnerable Sub-Saharan populatio
Keywords: African Research